Hotel Administration Application Design Using Delphi and UI/UX Designer - Rahmawati, Noni; Suroto, Suroto; Syah, Tamrin; Kurniawan, Tomi; Ramadani, Rio (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
The need for attractive and interactive Web Design is the dream of all service providers to get more customers. However, building the UI / UX Design requires software that can collaborate with the database, as well as having an interactive and attractive design, one of the software desired by Web Developers is Open-Source and can be developed for free and can be developed freely by the Web developer community. As developed here is using the Penpot App. In the Penpot App, we can build a Web design that is used as an easy display for web developers such as Layers and Assets. These layers talk about the appearance that will be used or the layout of some of the required components, while these Assets contain all Web components that can be dragged and dropped on the web layer that is being and will be built. Another component is Design and Prototype, these two components are to choose the right design as used to build the Hotel Website. In this Design we can use a Canvas background to determine the right color, hopefully with the UI/UX Designer use of Penpot can be perfect and follow the expectations of making the Hotel website, so that the percentage of visitors can increase by seeing the performance of the website built, other than UI/UX Designer. And administration system can use the Graphical User Interface Delphi by using the latest version.